CEU Graduation Ceremony 1998 - Part 2
The continuation of the CEU Graduation Ceremony of the Academic Year 1997/1998 held in the Museum of Applied Arts in Budapest on June 23, 1998. The recording starts with the conferring of CEU’s first three doctoral degrees (Stanko Andric, Margaret Dimitrova, Dragan Golubovic), continues with Prof. Sorin Antohi, CEU’s Academic Pro-Rector, announcing the students’ choice of Prof. Tibor Várady of the Legal Studies Department as “Professor of the Year 1997/1998” and ends with the final address of the evening given by Ambassador Donald M. Blinken, Chancellor, CEU Council. At the reception that followed, Prof. Tibor Várady, Dragan Golubovic, receiver of the doctoral degree and an MA graduate are being interviewed. Recordings from the Reception and the Graduation Party are included.